IMPLEMENTATION OF QIRO’AH HIKAYAH METHOD TO IMPROVE ARABIC READING SKILLS OF STEI PERMATA STUDENTS - Siti Imaniatul Muflihatin (STAI Al-Hidayat Lasem, 2022)
The results of this research are the steps for implementing qiro'ah hikayah in thisresearch, namely: 1. The researcher turned the material back, 2. The researcherasked the students to repeat what the researcher had read, 3. After that theresearcher asked the students to go up one by one to read the material. 4. Theresearcher gives questions from the material that is read. 5. The researcher askedstudents to collect answers. The results are assessed by dividing by 50%. (2) Thepercentage in cycle I can be seen that of the 36 students, 3 students completed thepercentage (8.33%), while the percentage that did not complete was (91.6%).Meanwhile, in cycle II there was an increase in student learning outcomes by apercentage (94.4%). Thus, the increase in student learning outcomes from cycle Ito cycle II was (86.07%). Therefore, in cycle II students' reading skills improve sothat they are said to be complete